Acessibilidade comunicacional para deficientes visuais: um estudo na Biblioteca Central da Universidade Federal da Paraíba - Cardoso, Adriana de Brito (2023)
In Brazil, education is everyone’s right guaranteed in the Federal Constitution of 1988, being an instrument that serves to improve people’s quality of life. It is through it that new mindsets and concepts about the differences that exist between people are created, therefore, investing in education is directly related to improving the well-being of society. In this sense, this research aimed to analyze communication accessibility within the scope of the UFPB Central Library regarding the provision of analog or digital services for blind or low vision users. It was applied research, whose approach to the problem was of a qualitative nature and, regarding the objectives, it had an exploratory and descriptive character. As for the technical procedures, we used the following data collection methods: Bibliographical and documental research, questionnaire and usability test, we also used the technique of direct observation and, for data analysis, we followed the method of content analysis, Bardin (1977).In the presentation of the results, at first, the main legal provisions in Brazil and international agreements regarding people with disabilities were analyzed, then the services offered by the UFPB Central Library were verified within the context of communication accessibility. In the second moment, the data collected through questionnaires and usability tests carried out by blind students or those with low vision, related to accessibility items in the digital services offered by the UFPB Central Library, were presented and analyzed. From the data collected, it was concluded that the Central Library, in line with the current PDI of the UFPB, has been seeking to improve its services in order to comply with the accessibility law with regard to communication accessibility, but it does not meet all the recommendations of communication accessibility provided for in international, guidelines, requiring adjustments and improvements in important issues, which today represent barriers to its blind users or those with low vision.